Integrated Healthcare Database Systems: A Review of Data Warehousing, Storage, and Integration Strategies - Ram Suman, Bikash (Jejaring Penelitian dan Pengabdian Masyarakat, 2025)
This paper provides a comprehensive review of current database systems and data warehousing technologies within the healthcare sector, emphasizing their roles in supporting forecasting and analytics. The objective is to describe, analyze, and evaluate the key features of these systems, particularly focusing on the essential functions of data storage and data integration in managing complex healthcare data environments. Recognizing that efficient data storage is fundamental to effective database management, the paper examines prevalent challenges within current healthcare systems, including issues related to data infrastructure, security, and interoperability. It further investigates how these challenges impact the reliability and accessibility of data crucial for informed decision-making. In addition to highlighting the difficulties, this review delves into the benefits and drawbacks of various data integration strategies. It discusses how advanced integration techniques can enhance data accuracy, streamline real-time access, and bolster analytical capabilities, while also addressing potential risks such as integration complexity and security vulnerabilities. By synthesizing the latest trends and research in database management, this paper aims to offer valuable insights for healthcare practitioners, IT professionals, and researchers. Ultimately, it seeks to guide the development of more secure, efficient, and resilient data management strategies that can better support healthcare analytics and forecasting in an increasingly data-driven industry.